The day of embryo transfer affects delivery rate, birth weights, female-to-male ratio, and monozygotic twin rate - Valentina Sotiroska; Zorancho Petanovski; Gligor Dimitrov; Makjuli Hadji-Lega; Damjan Shushleski; Stefan Saltirovski; Vladimir Matevski; Simona Shenbakar; Sasho Panov; Lars Johansson (Elsevier, 2015)
Objective: To compare the reproductive outcomes between the transfer of cleavage-stage embryos and blastocysts in two different age groups of patients. The reproductive capacity of women decreases by age. This decrease in capacity is directly related to a lower ovarian reserve and errors in the meiotic spindle of the oocyte, which increase chromosomal abnormalities and the formation of aneuploidy embryos with lower chances of implantation. Materials and Methods: A total of 1400 intracytoplasmic sperm injection cycles were analyzed. The study patients were divided into two age groups [aged < 36 years (Group I) and aged ≧ 36 years (Group II)]. The groups were subdivided according to the day of embryo transfer (ET)-Day 3 (ET3) and Day 5 (ET5). Results: In both age groups, transfer of blastocysts resulted in a higher clinical pregnancy rate and deliveries. An increased twin birth rate was observed in patients who were younger than 36 years on both transfer days compared with those who were older than 36 years of age. There was an elevated percentage of newborn males on ET5 in both age groups. Monozygotic twinning (MZT) rate was observed only among younger patients (<36 years of age), specifically on ET5 compared with ET3. There was no significant difference in the mean birth weight of singleton and twins between the ET3 and ET5 subgroups in the younger group of patients except for the triplets who were significantly heavier in the ET5 group compared with the older group (≧36 years of age) where significant difference was found only on the mean birth weight of singleton. Conclusion: The study suggests that if a blastocyst can be obtained in patients of advanced age (≧36 years), it improves their baby take-home rates. Younger patients (aged < 36 years) should undergo elective single blastocyst transfers to reduce multiple pregnancy rates.